Nitrous oxide emission from a transplanted rice field in alluvial soil as influenced by management of nitrogen fertiliser. (19th August 2016) - Bordoloi, N.; Baruah, K. K.; Maji, T. K.
Abstract: We investigated nitrous oxide (N2 O) emission from an irrigated rice field over two years to evaluate the management of nitrogenous fertiliser and its effect on reducing emissions. Four forms of nitrogenous fertilisers: NPK at the recommended application rate, starch–urea matrix (SUM) + PK, neem‐coated urea + PK and urea alone (urea without coating) were used. Gas samples were collected from the field at weekly intervals with the static chamber technique. N2 O emissions from different treatments ranged from 11.58 to 215.81 N2 O‐N μ g/m 2 /h, and seasonal N2 O emissions from 2.83 to 3.89 kg N2 O‐N/ha. Compared with other fertilisers, N2 O emissions were greatest after the application of the conventional NPK fertiliser. Moreover, SUM + PK reduced total N2 O emissions by 22.33% ( P < 0.05) compared with NPK during the rice‐growing period ( P < 0.05). The results indicate a strong correlation between N2 O emissions and soil organic carbon, nitrate, ammonium, above‐ and below‐ground plant biomass and photosynthesis ( P < 0.05). The application of SUM + PK in rice fields is suitable as a means of reducing N2 O emissions without affecting grain production.